2013
DOI: 10.3390/ijms14047603
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits GnRH-1, GnRH-3 and GnRH Receptor Expression in the Brain of the European Sea Bass, Dicentrarchus labrax

Abstract: Several evidences supported the existence of melatonin effects on reproductive system in fish. In order to investigate whether melatonin is involved in the modulation of GnRH systems in the European sea bass, we have injected melatonin (0.5 μg/g body mass) in male specimens. The brain mRNA transcript levels of the three GnRH forms and the five GnRH receptors present in this species were determined by real time quantitative PCR. Our findings revealed day–night variations in the brain expression of GnRH-1, GnRH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 51 publications
2
12
0
1
Order By: Relevance
“…Alternatively, the LPXRFamide mRNA from the terminal nerve/olfactory cells could exhibit daily variations in expression, being transcripts almost undetectable at particular moments of the day. In accordance, we previously reported the existence of day–night variations as well as melatonin effects on the expression of GnRH‐3 from the terminal nerve ganglion of sea bass (Servili et al, ). In addition, stimulatory actions of melatonin on the synthesis and release of GnIH have been described in birds (Chowdhury et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Alternatively, the LPXRFamide mRNA from the terminal nerve/olfactory cells could exhibit daily variations in expression, being transcripts almost undetectable at particular moments of the day. In accordance, we previously reported the existence of day–night variations as well as melatonin effects on the expression of GnRH‐3 from the terminal nerve ganglion of sea bass (Servili et al, ). In addition, stimulatory actions of melatonin on the synthesis and release of GnIH have been described in birds (Chowdhury et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The reproductive neuroendocrine systems of the European sea bass have been widely studied in past years (Servili et al, ). These studies have mainly focused on GnRH and kisspeptins (González‐Martínez et al, , , ; Carrillo et al, ; Servili et al, , ; Tena‐Sempere et al, ; Escobar et al, ; Alvarado et al, ). While GnRH and kisspeptin systems are considered the major hypothalamic factors stimulating pituitary gonadotropin release and reproduction in most vertebrates, studies in teleost fish have revealed the existence of an inhibitory control of the reproductive axis exerted by dopamine (Dufour et al, ).…”
mentioning
confidence: 99%
“…How does monochromatic light affect the expression of GnRH‐I in the chick hypothalamus? Previous research reported that melatonin inhibited GnRH‐1 expression in the brains of the European sea bass, and melatonin had an inhibitory effect on GnRH‐induced gonadotrophin release in rats . The present study found that GL significantly promoted melatonin secretion, whereas RL decreased plasma melatonin concentrations.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, this is the first study to show the influence of melatonin on GnRHR expression in sheep. However, the suppressory effect of melatonin on the GnRHR expression in the European sea bass [ 27 ] may indicate that the effect of melatonin on the expression of GnRHR is species-dependent. In humans, melatonin treatment enhances the human chorionic gonadotropin (hCG)-stimulated progesterone secretion with inhibition of GnRH and GnRH receptor expression.…”
Section: Discussionmentioning
confidence: 99%